The Relationship between Self-endangering Behaviours, Hopelessness Depression and Perceived Social Support in Adolescence - Longo, Ilenia; Orecchio, Susanna; Mafodda, Antonina Viviana; Sorrenti, Luana (Journal of Psychology and Psychotherapy Research, 2019)
Although the studies have investigated and identified the causes of risk and self-harm behaviours in adolescence, the relationship between Hopelessness Depression (HD), self-endangering behaviours, and the protective role that social support could play has not been sufficiently investigated. The aim of the present study is to investigate the relationship between risk and self-harm behaviours, HD and perceived social support in adolescent students. Furthermore, we want to investigate the predictive role of perceived social support and HD on risk and self-harm behaviours. The results showed that HD is positively related with the risk and self-harm behaviours and predicts them positively. Furthermore, it emerged that social support is negatively related with HD and risk and self-harm behaviours. Finally, the results showed that risk and self-harm behaviours are negatively predicted by instrumental support. Limitations and implications are discussed.